A mathematical model approach quantifying patients' response to changes in mechanical ventilation: Evaluation in volume support. Issue 4 (April 2015) - Larraza, S.; Dey, N.; Karbing, D.S.; Jensen, J.B.; Nygaard, M.; Winding, R.; Rees, S.E.
Highlights A mathematical approach may describe patient-response to changes in ventilation. The approach was evaluated in 12 patients on support ventilation. The approach includes changes in CO2 production, dead space and muscle-response. Data from patients' response were adequately described with the approach.